Developing a Strategy For Efficient Environmental Authorisation of Activities Affecting Wetlands in South Africa: Towards a Wise-Use Approach - Bramley Jemain Lemine (Obiter, 2020)
South Africa is a party to the Convention on Wetlands of International Importance especially as Waterfowl Habitat of 1971 (also referred to as the Ramsar Convention). Article 3(1) of the Ramsar Convention makes provision for the wise use of wetlands, which is defined as the “maintenance of the ecological character, achieved through the implementation of ecosystem approaches, within the context of sustainable development”. The Conference of the Parties has agreed on inherent weaknesses that could lead to the hampering of wise use. These weaknesses include, but are not limited to, authorities working in isolation; and the lack of communication between public and private sectors or technical personnel (environmental impact assessment specialists). Within the enabling provisions of South Africa’s EIA regulations, reference is made to “water source”, “water resource”, “wetland” and “ecosystem”. All these terms are read to include a wetland. However, whereas the terms “water source”, “water resource” and “wetland” are defined in the National Water Act 36 of 1998 (NWA), an “ecosystem” is defined in the National Environmental Management: Biodiversity Act 10 of 2004 (NEMBA), and “water source” is defined in the Conservation of Agricultural Resources Act 43 of 1983 (CARA). Furthermore, the administration of the NWA is with the Department of Water and Sanitation, while NEMBA is with the Department of Environment, Forestry and Fisheries, and CARA is with the Department of Agriculture, Land Reform and Rural Development. This multiplicity, combined with the application of the various specific environmental management acts (SEMAs), complicates the manner in which an EIA application is considered. This is so in that the national environmental framework casts the net wide in identifying the competent authority, but also in its effect on wise use decision making on activities pertaining to wetlands. In light of the aforementioned, this article aims to address the shortfalls and make recommendations that promote wise use.